LEMBAGA PENGAWAS HISBAH DAN RELEVANSINYA PADA DEWAN SYARIAH NASIONAL (DSN) DAN DEWAN PENGAWAS SYARIAH (DPS) DI PERBANKAN SYARIAH INDONESIA - Ririn Noviyanti (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2015)
All economic activity should be run in accordance with the Islamic values is a logical consequence for all Muslims, especially in Indonesia. In the past, in order to ensure economic activities run in eccordance to Islamic values, established oversight agencies (ḥisbah) at the time of the Prophet Muhammad (PBUH). With the rapid growth of Islamic banking in Indonesia nowadays. Then formed a special institution serves as overseeing the economic activity in the Islamic banks namely the National Sharia Board (DSN) and Sharia Supervisory Board (DPS).This study discusses the suitability DSN and DPS controlling techniques with hisbah controlling techniques during the classical era. Based on the study, can be concluded that: (1) hisbah have significant roles and functions in creating a fair economy (2) DSN and DPS has a role and function as a supervisor in the activities economies Islamic banks in Indonesia. (3) there is a relevance role and function between DPS DSN institutions with technical what was done by hisbah institutions in the classical era.